Desenvolvimento econômico, integração comercial e desigualdades regionais: Angola no contexto da África Austral - Ambrósio, Heitor Simão Afonso (2014)
The topic explains a number of factors that influence on trade integration and regional inequalities both in Southern Africa and in Angola. So is this part of Africa that Angola is part where we find the Development Community (SADC). Although this is the most emerging economic bloc on the continent still presents major inequalities mainly in the field of trade integration, setting off on a very slow socioeconomic development and a less conjugated equality among their members, despite the efforts of the governments of this community. In general, governments have made tremendous efforts to reduce these effects, but the indicators still show that they are far from reaching them. Regarding regional differences in Angola, it was found that due to certain economic operations since 2002, comes to registering significant increases in Gross Domestic Product mirroring in large sums of wealth that the country has accumulated in recent years. However, this wealth does not bring about significant changes in infrastructure to support economic development, such as in the energy and water supply among others, creating in this way, vast inequalities between regions, influencing in some way the quality of life the populations of some regions. Furthermore, the analyzed data indicate that regions always showed signs of development since colonization remain the same and, in the case of the Metropolis and the Central East region where the main capital of Angola. However, it is observed that much of the wealth of the country since the colonial era mostly less developed, eg, the North (coffee and oil as the main sources of wealth of the country) and Middle East region has regions (mainly in Lunda Norte and Lunda Sul -. diamond mining and non-oil energy, etc.) thus creating a paradox. Despite these inconsistencies, the government has proved very engaged in ways to eliminate the major factors that have influenced these very striking inequalities between regions. Thus, the study aims to examine regional inequalities in the context of southern Africa and in Angola, scaling inequalities in economic development, especially economic activity and infrastructure. Moreover, the method most widely used in the research was to collect data through the analysis of documents, in addition to books and articles. Some of the results indicate that in terms of trade, the countries of the region are not willing to trade among themselves, since many of them are in disadvantage against the other. In Angola, the origin of inequality is not new, however, already has a long history, from the time of Portuguese colony and civil war. Thus, it is recommended that regions of Africa in general must unite and create policies that make up the reality of the continent itself. Regarding Angola, the state should create favorable conditions for economic infrastructure as quickly as possible in order to reduce regional disparities.